Huge vaginal stone: Case report and review of the literature - Jo, Jae Yoon; Lee, Seon Mi; Shin, Jeong Kyu; Choi, Won Jun; Cho, In Ae (Frontiers in Surgery, 2022)
Primary vaginal stones have been rarely reported; the reports that do exist are usually case reports. Because of their low incidence, they are often misdiagnosed. This case report and literature review of a primary vaginal stone presents an assessment of symptoms and common risk factors for vaginal stone formation. A 28-year-old woman with spastic quadriplegia who had been bedridden for most of her life presented to the emergency department for abdominal distension and fever. She had chronic constipation, recurrent urinary tract infections (UTIs), and vaginal discharge. Abdominopelvic computed tomography (CT) was performed and a large stone observed. The vaginal stone was completely removed through the vaginal stump after hysterectomy. Differential diagnoses of vesicovaginal fistula, urethrovaginal fistula, genital anomaly, and ectopic ureter were made by performing several tests using indigo-carmine dye. She recovered from surgery without any complications. There was no recurrence of vaginal stones after 3 months. A biochemical analysis reported that the vaginal stone was 100% struvite. Vaginal stones are caused by repeated infections in an environment in which urine collects gradually. Patients with recurrent UTIs who are bedridden should be able to prevent vaginal stones with periodic gynecological examinations for early diagnosis and management.